Politik Demokrasi: Membangun Solidaritas dan Sinergi Di Tengah Pendemi Covid-19 - Stepanus Angga (Forum, 2021)
My focus in this paper is on the politics of democracy and how to build solidarity and synergy in the midst of the Covid-19 pandemic. Because it is a political task to handle any difficult situation, including this pandemic. The methodology of this paper begins with a little understanding of the outbreak of a virus which is the great enemy of mankind with its deadly historicity in the history of human civilization. In the next part, the author enters the realm of our politics during this pandemic. Politics that emphasizes the people, of course, begins with a rational discourse and is able to understand the social context. This difficult situation also invites people to have the same feeling, namely the sense of crisis. This feeling invites people to build and encourage each other. From this methodology, I propose two important ideas, namely first to always pay attention to civil society to its fullest and second, our government must build synergy and internal government coordination that runs well.